Investigation of the Proliferation, Apoptosis/Necrosis, and Cell Cycle Phases in Several Human Multiple Myeloma Cell Lines. Comparison of Viscum album QuFrF Extract with Vincristine in an In Vitro Model - Eva Kovacs (The Scientific World Journal)
Multiple myeloma is a haematological disorder of malignant plasma cells. Interleukin-6 (IL-6) is a potent growth factor for the proliferation of these cells. Vincristine as a chemotherapeutic agent is used mainly in combination with other chemotherapeutic substances in the treatment of different haematological disorders. Viscum album QuFrF (VAQuFrF) extract is an experimental drug that is not used in the treatment in tumour patients. It contains 2000 ng lectin and 10 µg viscotoxin in 10 mg extract. In this study, the effects of VAQuFrF extract were compared with those of vincristine in six human multiple myeloma cell lines (Molp-8, LP-1, RPMI-8226, OPM-2, Colo-677, and KMS-12-BM) using an in vitro model. As parameters, the IL-6 production, proliferation, apoptosis/necrosis, and cell cycle phases of the cells were taken. To measure the IL-6 production, apoptosis/necrosis, and cell cycle phases, the substances were tested in dose ranges of 10, 50, and 100 µg/106 cells. To measure the proliferation of the cells, the substances were tested in dose ranges of 1, 5, and 10 µg/105 cells. The profile of the antitumour effects of the two substances is identical. (1) Neither VAQuFrF extract nor vincristine produced IL-6 in any cell line. (2) Both substances inhibited the proliferation of the cells (cytostatic effect), arrested the cell cycle phases, and increased the number of apoptotic/necrotic cells (cytocidal effect). At a dose of 10 µg/105 cells, VAQuFrF more effectively inhibited the proliferation than vincristine (p < 0.01) in the cell lines Molp-8, LP-1, and RPMI-8226. (3) VAQuFrF affected the tumour cells mainly via cytostatic effect. Vincristine had a clear cytocidal effect. These findings indicate that VAQuFrF extract could be a novel drug in the treatment of multiple myeloma.